PENGARUH VARIASI KARAGENAN DAN HFS (HIGH FRUCTOSE SYRUP) TERHADAP PEMBUATAN PERMEN JELLY BERBASIS NIRA KELAPA SAWIT - Dovianda, Kevin Tegar; Raja, Pada Mulia; Syukri, Muhammad; Fachrizal (Institut Teknologi Sawit Indonesia (ITSI), 2024)
In this study, the utilization of oil palm resources will be carried out. One of them is by using palm sap into jelly candy. The purpose of this study was to study the manufacture of jelly candy based on palm sap and to find out the best composition of Carrageenan and HFS in the manufacture of jelly candy based on palm sap. The stages of this research were starting from sap sampling, making jelly candy, sample testing and data processing. The method used in this study was a factorial completely randomized design (CRD) and consisted of 2 factors, each factor having 3 variations. Carrageenan Factor : K1 : 2 %, K2 : 4 % and K3 : 6 %. HFS factor : H1 : 20 %, H2 : 25 %, H3 : 30%. The test was carried out 3 times. Sample testing includes water content, vitamin c content, and organoleptic tests for aroma, taste and texture. From the results of research conducted on 9 treatments: K1H1, K1H2, K1H3, K2H1, K2H2, K2H3, K3H1, K3H2 and K3H3. The interaction of the addition of carrageenan and HFS has no significant effect on the moisture and vitamin C content of jelly candy based on palm sap. There was no interaction that had a significant effect on the addition of Carrageenan and HFS due to the different functions of the ingredients, Carrageenan served to thicken the jelly candy and HFS served to give a sweet taste to the jelly candy. The higher concentration of Carrageenan given is directly proportional to the high content of reducing ash and the higher concentration of HFS given is directly proportional to the high content of reducing sugar. Organoleptic test of taste and aroma all panelists gave normal assessments for all samples, organoleptic test of sample texture K1H1, K1H2, K1H3, dan K2H1 has an abnormal texture, sample K2H2, K2H3, K3H1, K3H2 dan K3H3 has a normal texture. The best treatment is in the K3H3 treatment, the addition of 6% carrageenan & 30% HFS, with a water content of 19.74%. Ash content 1.73%, Vitamin C 1.05%, Reducing sugar 64.19%, organoleptic test value of aroma (normal), taste (normal) and texture (normal). Key words : Palm Sap, Jelly Candy, Carrageenan, High Fructose Syrup